Malaysia Corporate Credibility Index : An Assesment - Dayang Affizzah, Awang Marikan; Fathan, Soetrisno; Irma Yazreen, Binti Md Yusoff; Winnie, Nirau (Macrothink Institute, Inc., 2019)
Corporate credibility has attracted interest from a wide range of academic disciplines. Malaysians tend to identify themselves by ethnic groups and not nationality. Cross-national marketing research that attempts to make comparisons and generalizations about Malaysian consumers, instead of Malay, Chinese or Indian sub-groups, is likely to be questionable. As corporate credibility index is crucial for every corporate, there is no benchmark or index in Malaysia context in determining levels of credibility of corporates. This provides an opportunity for this research to assess measurement invariance in cross-ethic perception difference between the westerner and Malaysian as well as developing a credibility index model called Malaysia organization credibility Index (MOCI) as an output of research. The Asian perception on corporate credibility may not be reliable and suitable if it is tested using the western-based scales, due to differences in ethnic culture, religious and personal values of the Asian consumers themselves. Nonetheless, one must determine whether such scales exhibit cross-cultural equivalence before meaningful comparisons and generalizations can be made. Based on the SEM, the study finds out that both westerners and Asian seems to share the same perception on the honesty, trustworthiness and expertise. However, Asian perceived to see that customer and employees focus are the significant variables in perceiving the credibility of corporate organization and its reputation. Hence, increasingly, corporations in Asia will need to be cognizant of how they are perceived to achieve their strategic goals. This will involve understanding the impact of specific country reputations on firm reputation. Thus this study suggests the establishment of Malaysian Corporate Credibility Index that can be applied to Asian as a whole.